Communicating Science and Technology. Gradiva’s Books of Popularization of Science and Technology and the Portuguese Public - Navalhas Inês N. (HoST, 2019)
By focusing on the books of popularization of science and technology published by Gradiva this research aims at understanding the mechanisms and strategies to bring science and technology to a broader audience in Portugal, after 1974, the year of the Carnation Revolution that put an end to a long half century dictatorship. I use a mix conceptual framework: on the one hand, I use the scientific literacy and public understanding of science and technology main references to explore the public’s behavior and opinion concerning scientific and technological knowledge; on the other hand, I analyze Gradiva’s choices concerning the collections aimed at popularizing science and technology. So, I hope to contribute to map the perception of the Portuguese public about techno-scientific themes that influence their life and decisions, to understand how scientists relate to scientific and technological popularization literature and to assess scientific literacy in the Portuguese population.